KAJIAN LITERATUR TRANSFORMASI PEMBELAJARAN KIMIA MELALUI PENDEKATAN GREEN CHEMISTRY UNTUK PEMBANGUNAN BERKELANJUTAN - Febri (Universitas Samudra, 2026)
Green Chemistry is a strategic approach to revitalizing chemistry learning to make it more relevant to sustainability issues. This literature review aims to analyze the concept, implementation, and impact of Green Chemistry's application in chemistry education over the past five years. The study method was conducted by reviewing various national and international scientific publications. The results of the study indicate that the integration of Green Chemistry can improve students' scientific literacy, environmental awareness, critical thinking skills, and 21st-century competencies. Furthermore, this approach strengthens the relationship between chemical theory, environmentally friendly laboratory practices, and the objectives of the Sustainable Development Goals (SDGs). This study emphasizes the importance of transforming chemistry curriculum and pedagogy through Green Chemistry to create human resources with a global perspective and sustainability.